Discontinuity-embedded reduced-order PINNs for intelligent diagnosis of longitudinal structural mechanical state in jointed segmental tunnels - Zhiwei Zhang; Xuesong Cheng; Tianqi Zhang; Shida Li; Min Sun; Jianqiu Wu; Wei Wang; Gang Zheng (Tunnelling and Underground Space Technology, 2026)

High-level expression of zearalenone lactonohydrolase ZenG in Pichia pastoris via combinatorial strategy - Qin Zhou; Shida Zhao; Yuzhuo Wu; Yanfei Sun; Qi Wu; Qi Li; Ding Li; Jianhong Xu (Archives of Microbiology, 2026)

Excess vehicular evaporative emissions for prolonged parking during the COVID-19 lockdown in China - Pengfei Song; Jianfei Peng; Yan Liu; Chongzhi Zhong; Qiang Chen; Chao Zou; Shida Sun; Yajun Wu; Yao Gu; Taiyu Zhang; Ning Yang; Hongjun Mao (Journal of Hazardous Materials, 2025)

Synergistic reduction of air pollutants and carbon dioxide emissions in Shanxi Province, China from 2013 to 2020 - LiLing Wu; Shida Sun; Gaige Zhang; Zimu Jia; Yuyun Liu; Chenxi Xu; Mengjie Guo; Luyao Zhang; Cilan Cai; Runcao Zhang; Jialin Zheng; Wenjie He; et al. (Science of The Total Environment, 2024)

Genesis and accumulation mechanism of external gas in deep coal seams of the Baijiahai Uplift, Junggar Basin, China - Bin Zhang; Shu Tao; Bin Sun; Shuling Tang; Shida Chen; Yijie Wen; Jincheng Ye (International Journal of Coal Geology, 2024)

Evaluating traffic emission control policies based on large-scale and real-time data: A case study in central China - Chao Zou; Lin Wu; Yanan Wang; Shida Sun; Ning Wei; Bin Sun; Jingwei Ni; Jing He; Qijun Zhang; Jianfei Peng; Hongjun Mao (Science of The Total Environment, 2023)

Production and application of mouse monoclonal antibodies targeting linear epitopes in pB602L of African swine fever virus - Pengfei Wang; Chunguo Liu; Shida Wang; Lili Wen; Zhibin Shi; Yue Chi; Ming Wang; Zaisi Liu; Zhenzhao Sun; Lili Wei; Decheng Yang; Xijun He; et al. (Archives of Virology, 2022)
African swine fever (ASF) is an acute hemorrhagic disease of domestic pigs. The causative agent of ASF, ASF virus (ASFV), is a double-stranded DNA virus, the sole member in the family Asfarviridae . The non-structural protein pB602L of ASFV is a molecular chaperone of the major capsid protein p72 and plays a key role in icosahedral capsid assembly. This protein is antigenic and is a target for developing diagnostic tools for ASF. To generate monoclonal antibodies (mAbs) against pB602L, a prokaryotically expressed recombinant pB602L protein was produced, purified, and used as an antigen to immunize mice. A total of eight mouse mAbs were obtained, and their binding epitopes were screened by Western blot using an overlapping set of polypeptides from pB602L. Three linear epitopes were identified and designated epitope 1 ( 366 ANRERYNY 373 ), epitope 2 ( 415 GPDAPGLSI 423 ), and epitope 3 ( 498 EMLNVPDD 505 ). Based on the epitope recognized, the eight mAbs were placed into three groups: group 1 (B2A1, B2F1, and B2D10), group 2 (B2H10, B2B2, B2D8, and B2A3), and group 3 (B2E12). The mAbs B2A1, B2H10, and B2E12, each representing one of the groups, were used to detect pB602L in ASFV-infected porcine alveolar macrophages (PAMs) and pig tissues, using an indirect fluorescence assay (IFA) and immunohistochemical staining, respectively. The results showed that pB602L was detectable with all three mAbs in immunohistochemical staining, but only B2H10 was suitable for detecting the proteins in ASFV-infected PAMs by IFA. In summary, we developed eight anti-pB602L mouse mAbs recognizing three linear epitopes in the protein, which can be used as reagents for basic and applied research on ASFV.

A nonlinear coupled soil moisture-vegetation model - Liu Shikuo; Liu Shida; Fu Zuntao; Sun Lan (Advances in Atmospheric Sciences, 2005)